2012
DOI: 10.3382/ps.2012-02204
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in breast muscle associated with feed efficiency in a single male broiler line using a chicken 44K microarray. II. Differentially expressed focus genes

Abstract: Global RNA expression in breast muscle obtained from a male broiler line phenotyped for high or low feed efficiency (FE) was investigated using microarray analysis. Microarray procedures and validation were reported previously. By using an overlay function of a software program (Ingenuity Pathway Analysis, IPA) in which canonical pathways are projected onto a set of genes, a subset of 27 differentially expressed focus genes were identified. Focus genes that were upregulated in the high FE phenotype were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 83 publications
4
59
2
Order By: Relevance
“…Additionally, increased expression of adipose genes showed that PeM muscles may retain increased mass of adipose tissues, where the wooden breast myopathy showed increased occurrence of irregular adipose tissue throughout the muscle [19]. Higher expression of NOXO1 (NADPH oxidase organizer 1) indicates that oxidative stress and scavenging antioxidants are closely associated with feed efficiency, which has been reported previously [2, 3, 5]. PCSK1 (proprotein convertase subtilisin/kexin type 1) is not restricted to the expression in muscle tissues, and its functions in glucose and lipid metabolism [20, 21] implies that PeM muscle has more active cellular pathways for energy metabolism.…”
Section: Resultsmentioning
confidence: 71%
“…Additionally, increased expression of adipose genes showed that PeM muscles may retain increased mass of adipose tissues, where the wooden breast myopathy showed increased occurrence of irregular adipose tissue throughout the muscle [19]. Higher expression of NOXO1 (NADPH oxidase organizer 1) indicates that oxidative stress and scavenging antioxidants are closely associated with feed efficiency, which has been reported previously [2, 3, 5]. PCSK1 (proprotein convertase subtilisin/kexin type 1) is not restricted to the expression in muscle tissues, and its functions in glucose and lipid metabolism [20, 21] implies that PeM muscle has more active cellular pathways for energy metabolism.…”
Section: Resultsmentioning
confidence: 71%
“…Altogether, this suggests diminished oxidative stress in more efficient pigs. In agreement with this assumption, research in broilers has consistently shown that muscle mitochondria from high efficient birds produce less hydrogen peroxide [37]. In addition, others have shown that ROS production in muscle and RFI values were positively correlated, although no difference in electron leakage was seen in mitochondria prepared from livers of low and high RFI pig lines [38].…”
Section: Discussionmentioning
confidence: 76%
“…A specific example of this includes the UQCRQ gene, which was identified as differentially expressed in the muscle tissue from these animals and displayed the same direction of expression in all cohorts [5]. Oxidative stress has been proposed in many other studies as a factor that affects feed efficiency in swine, poultry, and beef cattle [25][26][27][28][29][30].…”
Section: Genes/pathways Identified For Gainmentioning
confidence: 95%